Replication Data for "Fertilizer Policy Reforms in the Midst of Crisis: Evidence from Rwanda" - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
This dataset is provided to support the replication of the results presented in the paper "The Impact of Fertilizer Subsidies on Agricultural Productivity in Rwanda" (Spielman, David J.; Mugabo, Serge; Rosenbach, Gracie et al., forthcoming). It includes both the raw data and the processed variables used in the analysis.